An Archaeological and Historical Examination of the Sulphur Fork Factory, 1817-1822 - Jones, Rachel E. (My University, 2023)
The United States Indian Factory System, an early experiment in public enterprise, was a late addition to the North American Fur Trade phenomenon. Created by an act of Congress in 1795, the factory system established a total of thirty-one trading posts, a majority of which were located along the Mississippi River and its western tributaries. It was part trade, part foreign policy, and part expansionist ideology. And it was among the earliest legislated acts governing relations with native peoples. This thesis focuses on the history and archaeology of the Sulphur Fork Factory (1817-1822), strategically located in present day southwest Arkansas. The Sulphur Fork Factory was identified and uncovered by an amateur archaeologist in 1988 and recorded as site 3M1266. With the development and utilization of ceramic chronology we can identify the site’s period of occupation, which spanned around 100 years. A period of use well beyond the Sulphur Fork Factory’s eight years of government occupation and operation. The record – both historical and archaeological – for factory store sites in the southeastern United States is limited. This thesis inches forward and documents one factory’s role in the region.
Keywords: North American Fur Trade; United States Indian Factory System; Sulphur Fork Factory; Southeastern Historical Archaeology